2020
DOI: 10.1007/s11940-020-00641-5
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Systematic Review with Meta-Analysis of Symptoms Prevalence in Covid-19: the Relevance of Olfactory Symptoms in Infection Not Requiring Hospitalization

Abstract: Purpose of review To investigate the association between the olfactory dysfunction and the more typical symptoms (fever, cough, dyspnoea) within the Sars-CoV-2 infection (COVID-19) in hospitalized and non-hospitalized patients. Recent findings PubMed, Scopus and Web of Science databases were reviewed from May 5, 2020, to June 1, 2020. Inclusion criteria included English, French, German, Spanish or Italian language studies containing original data related to COVID19, anosmia, fever, cough, and dyspnoea, in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 43 publications
4
23
0
Order By: Relevance
“…The study design, sample size, recruitment setting (inpatients vs. outpatients), and model of testing smell sensation (self-reporting survey vs. physical exam) could signi cantly affect the results. It was found that anosmia was more common in non-hospitalized individuals than hospitalized ones with COVID-19 (39,40). Our study showed that loss of smell and taste was associated with reduced odds of severe cases and death due among hospitalized cases.…”
Section: Discussionsupporting
confidence: 45%
“…The study design, sample size, recruitment setting (inpatients vs. outpatients), and model of testing smell sensation (self-reporting survey vs. physical exam) could signi cantly affect the results. It was found that anosmia was more common in non-hospitalized individuals than hospitalized ones with COVID-19 (39,40). Our study showed that loss of smell and taste was associated with reduced odds of severe cases and death due among hospitalized cases.…”
Section: Discussionsupporting
confidence: 45%
“…This result was almost thrice the initial prevalence reported from Wuhan, China 174 , 208 . This suggests that anosmia is a potential indicator of SARS-CoV-2 infection, and may be useful for screening and early identification of COIVD-19 patients, particularly asymptomatics 241 . Some countries, such as the UK and US have used anosmia as an indicator for preventive measure, wherein COVID-19 patient with anosmia should commence self-isolation 242 - 244 .…”
Section: Discussionmentioning
confidence: 98%
“…COVID-19 symptoms are highly variable, although the most commonly reported include fever, cough, fatigue, breathing difficulties, and loss of smell and taste. 3 While many individuals report mild symptoms 1 to 14 days after viral exposure, unfortunately a large portion of the affected population develops acute respiratory distress syndrome (ARDS). 4 If not treated promptly and efficiently, ARDS can dramatically turn into cytokine storms, 5 multiorgan failure, 6 septic shock, 7 and blood clots.…”
mentioning
confidence: 99%